Epidemiology and risk factors of coccyx fracture: A study using national claim database in South Korea. Issue 10 (October 2020) - Won, Heejae; Moon, Sun-Young; Park, Jae Hyun; Kim, Jin-Kak; Kim, Hong Seok; Baek, Seung-Hoon; Kim, Shin-Yoon; Lee, Young-Kyun; Koo, Kyung-Hoi
Highlights: The incidence and epidemiologic patterns of coccyx fracture is not known. In this study, the annual incidence was 119.75/100, 000; 33.44/100, 000 in male and 86.30/100, 000 in female. The male to female ratio was 1:2.6. The incidence rate was the highest at puberty (age of 10-14 years) in male and at menopause (age of 50-54 years) in female. The coccyx fracture was frequent in winter followed by summer. In generalized linear model, old age, female gender, recent year, summer and winter, low temperature and high amount of precipitation appeared as risk factors for coccyx fracture. Abstract: Introduction: Coccyx fracture usually is a low-energy trauma caused by a backward fall onto a slippery floor of ice. The exact epidemiology of the coccyx fracture is not known. Moreover, the effects of seasonality and weather on the fracture incidence have not been reported. The purpose of this study was to evaluate the annual incidence, gender-preponderance, age-distribution, seasonal variation and climatic risk factors of the coccyx fracture. Methods: We identified coccyx fractures, which occurred in South Korea from 2010 to 2018, using nationwide data of Korean Health Insurance Review and Assessment Service (HIRA). International Classification of Diseases-10th Revision (ICD-10) code S322 was used for the identification. Annual incidence of the coccyx fracture was calculated, and the fractures were correlated with gender, age, month of diagnosis and climatic factors. Results: A total of 238, 906 patients were diagnosed with coccyx fracture with an average of 26, 545 patients at year. Male to female ratio was 1:2.6. The annual incidence of coccyx fracture was 119.75/100, 000 persons in 2018; 33.44/100, 000 in male and 86.30/100, 000 in female. The incidence rate was the highest at puberty (age of 10-14 years) in male, and at menopause (age of 50-54 years) in female. The incidence was frequent in winter followed by summer. The incidence of coccyx fracture was negatively correlated with the temperature (Pearson correlation factor= -0.67, P <0.01) in winter, while it was positively correlated with the temperature in summer (Pearson correlation coefficient = 0.66, p <0.01). In generalized linear model, old age, female gender, recent year, summer and winter, low temperature and high amount of precipitation appeared as risk factors for coccyx fracture. Conclusions: The epidemiologic patterns of coccyx fracture were comparable to other osteoporotic fractures. Findings of our study can be used for epidemiological awareness and prevention campaigns of coccyx fracture.